Determinants of New Consumer Product Success or Failure in Nepal - Sharma, Bed Nath (Journal of Nepalese Business Studies, 2007)
This study is concerned to know the determinants of new product success or failure in Nepalese market. New product success or failure is measured financially. The main determinants of new product success are: product features, price, quality promotion, market information, service to customers, wide distribution channel etc. Most of the new products are sick or partially successful due to lower quality, high competition, improper pricing, weak promotional efforts, ineffective advertisement media, irregular supply of goods, financial inadequacy, insufficient market research, less beneficial to the users etc. Few new products are successful which is indicated by market growth, competitive position maintained, profitability etc. Journal of Nepalese Business Studies 2006/III/1 pp. 70-77